Pelatihan Kewirausahaan Berperspektif Gender: Perhitungan Harga Produksi Dan Pembukuan Bagi Pemuda/I Usia Produktif Pelaku Usaha Di Kota Jayapura - Cornelia D. Matani; Pascalina Van Sweet Sesa (The Community Engagement Journal, 2022)
This service activity aims to train the community, especially young people in productive age for identifying and calculating production costs and carrying out bookkeeping for recording their business transactions for product and service businesses. This training was held at 12th -14th of April 2021at Magister Akuntansi building, Abepura, Jayapura city. The participants of the activity were 19 youths aged 19-20 years. The training was carried out by introducing the basic concept of gender in business and the equal role of women and men in running their businesses. Furthermore, this training trains participants to calculate the business costs of products and services and then collect these costs into production costs. The following training is about making a bookkeeping for running a business which is needed to determine the financial condition of the business and as a basis for evaluating the state of the business. The mechanism for monitoring and evaluating training activities is carried out through the distribution of pre and post test questionnaires which are distributed for training the participants before and after the activity.